Why video health education messages should be considered for all dental waiting rooms. - Michelle McNab; Tony Skapetis (PLoS ONE, 2019)
Objective Video is an effective, accessible, and low cost method of delivering health education messages to a wide audience. Dental waiting rooms provide an opportunity to deliver video oral health education interventions to receptive viewers. In this study we aim to evaluate firstly video oral health education in regards to patient preference, and secondly its ability to change both immediate and sustained self-reported intended health behaviours by patients. Method Data from 253 individuals from a public hospital dental waiting room were gathered using a previously validated survey following an oral health education video intervention, and analysed using descriptive analysis, Fischer's Exact Test, and Wilcoxon Signed Ranks Test across 3 time intervals. Results Participants across all ages evaluated the video oral health education approach as easy to follow and understand (p<0.001), the content practical and useful (p<0.001), and that it was a better experience (p<0.01). Those watching between 5 and 20 minutes reported that video was the best format to present oral care information (p<0.02). At follow up, significant improvement in the tools used by participants to clean teeth was seen (39.8%, p<0.001), as well as reported reduction in sweet consumption frequency (21.3%, p<0.001) and in smoking (44.8%, p<0.02). Conclusion Video format oral health education used in dental waiting rooms was found to be effective in educating patients and instigating both immediate and sustained self-reported behaviour change. Significant improvement in tools used for oral hygiene and a reduction in sweets consumption were demonstrated, both of which are essential factors in reducing caries rates and improving oral health.